Tropomodulins and Tropomyosins: Working as a Team - Colpan, Mert (J Muscle Res Cell Motil, 2013)
Actin filaments are major components of the cytoskeleton in eukaryotic cells and are involved in vital cellular functions such as cell motility and muscle contraction. Tropomyosin is an alpha-helical, coiled coil protein that covers the grooves of actin filaments and stabilizes them. Actin filament length is optimized by tropomodulin, which caps the slow growing (pointed end) of thin filaments to inhibit polymerization or depolymerization. Tropomodulin consists of two structurally distinct regions: the N-terminal and the C-terminal domains. The N-terminal domain contains two tropomyosin-binding sites and one tropomyosin-dependent actin-binding site, whereas the C-terminal domain contains a tropomyosin-independent actin-binding site. Tropomodulin binds to two tropomyosin molecules and at least one actin molecule during capping. The interaction of tropomodulin with tropomyosin is a key regulatory factor for actin filament organization. The binding efficacy of tropomodulin to tropomyosin is isoform-dependent. The affinities of tropomodulin/tropomyosin binding influence the proper localization and capping efficiency of tropomodulin at the pointed end of actin filaments in cells. Tropomodulin and tropomyosin are crucial constituents of the actin filament network, making their presence indispensable in living cells. Here we describe how a small difference in the sequence of the tropomyosin-binding sites of tropomodulin may result in dramatic change in localization of Tmod in muscle cells or morphology of non-muscle cells. We also suggest most promising directions to study and elucidate the role of Tmod-TM interaction in formation and maintenance of sarcomeric and cytoskeletal structure.